Short Story Classics (American) Vol. 2 - Patten, William, 1868-1936 (Salt Lake City, UT : Project Gutenberg, 2005)
"Short Story Classics (American) Vol. 2" by William Patten is a collection of short stories written in the early 20th century. This anthology features a variety of narratives from notable American authors, showcasing themes of life, identity, love, and the complexities of human emotions against the backdrop of America$1 (Bs rich cultural tapestry. The opening of the anthology introduces one of its featured stories, "The Brigade Commander" by J.W. De Forest, which is set during the Civil War. The narrative follows Colonel Waldron, a complex figure admired for his military prowess but steeped in personal turmoil, as he prepares for battle with his regiment. Meanwhile, intimate tensions build between Waldron and Captain Fitz Hugh, who share a complicated past involving love and betrayal, setting up a high-stakes scenario filled with impending conflict, not just on the battlefield but also in their intertwined personal lives. The stage is set for a vivid exploration of camaraderie, duty, and the moral dilemmas faced by soldiers in war, which resonates throughout De Forest's storytelling. (This is an automatically generated summary.)s
The Brigade Commander, by J. W. Deforest -- Who Was She?, by Bayard Taylor -- Mademoiselle Olympe Zabriski, by Thomas Bailey Aldrich -- Brother Sebastian's Friendship, by Harold Frederic -- A Good-For-Nothing, by Hjalmar Hjorth Boyesen -- The Idyl Of Red Gulch, by Bret Harte -- Crutch, The Page, by George Alfred Townsend ("Gath") -- In Each Other's Shoes, by George Parsons Lathrop -- The Denver Express, by A. A. Hayes -- Jaune D'antimoine, by Thomas Allibone Janvier -- Ole 'Stracted, by Thomas Nelson Page -- Our Consul At Carlsruhe, by F. J. Stimson ("J. S. Of Dale").
Release date is 2005-08-20
Produced by Michael Gray
Keywords: Short stories, American